The implications of the structure of the regulatory expropriation enquiry in international investment law - Bonnitcha, J; Jonathan Merrington Bonnitcha (2008)
This thesis examines the structure of enquiry that arbitral tribunals use to distinguish between regulatory expropriation and legitimate non-compensable regulation in international investment law. The thesis proposes a new taxonomy of the possible structures of enquiry: the enquiry could look exclusively to the effects of the measure on the protected property; exclusively to the characteristics of the impugned measure; or to both the effects on the property and the characteristics of the measure. The application of this taxonomy shows that there is no agreed structure of enquiry in decisions on regulatory expropriation in international investment law. However, various threads of jurisprudence do show some degree of internal consistency. The thesis identifies six approaches in the decisions of arbitral tribunals: two that look exclusively to the effects of the measure; one that looks exclusively to the characteristics of the measure; and three that consider both the effects and the characteristics of the measure. Of the three approaches that consider both the effects and the characteristics of a measure, one is a direct adoption of US 5th Amendment jurisprudence and another is a direct adoption of ECHR Article 1 – Protocol 1 jurisprudence. Chapters 4 and 5 examine the jurisprudence of the US and ECHR in detail. These chapters show that, unlike international investment law, each of these jurisdictions has an established structure of enquiry in cases of regulatory expropriation. All six approaches to regulatory expropriation are sketched as models. These model approaches are applied to the case study of Piero Foresti. The case study demonstrates the most significant conclusion of this thesis: that different structures of enquiry, and different approaches within those structures, necessarily entail different legal outcomes on the same facts.